Analyze the detection performance of network radar on Rician targets - LIU Yue-ping1; JIANG Qiu-xi1; BI Da-ping1; CUI Rui1 (Tongxin xuebao)
The detection performance of the four different kinds of network radar models on Rician targets was analyzed when the total power of the transmitters was definite.The simulated and analyzed results show that Rician targets can be divided into two kinds which have different detection performance.In the network radar,the detection performance of class-Rayleigh targets is like Rayleigh targets,and the detection performance of standard Rician targets is different from Rayleigh targets.